A transdiagnostic cognitive behaviour therapy-based intervention in a secondary-care mental health service. (2016) - Garner, Emily; Gillmore, Chris; Lomax, Claire
Abstract: Due to the growing evidence base supporting the hypothesis of common processes across different mental health problems, transdiagnostic interventions are receiving increased research attention. Transdiagnostic approaches have the potential to produce better outcomes, to reduce waiting times and to increase cost-effectiveness in stretched mental health services. Research into transdiagnostic cognitive behaviour therapy (CBT) in group format has demonstrated positive results in participants with anxiety disorders, with some studies extending the inclusion criteria to secondary and comorbid symptoms. This study evaluates a transdiagnostic CBT-based intervention, delivered by a secondary-care mental health team and includes participants with a range of diagnoses typical of this population. The real-world setting and lack of exclusion criteria based upon diagnosis provides an ecologically valid evaluation of a transdiagnostic CBT-based intervention. The results suggest that the intervention was associated with reductions in self-reported symptomatology and improvements in social functioning of individuals who attended in a secondary-care mental health service.